A summer in the cage - Selkow, Ben; Mims, John; 34lukefilms (Firm); Sundance Channel; Soundview Media Partners ([New York, N.Y.?] : 34lukefilms, 2007)
Ben Selkow starts out making a documentary about an inner city basketball court called "the cage." There he meets Sam and the focus of the story becomes Sam's battle with bipolar disorder. The film follows Sam for seven years as he suffers delusional manic episodes, battles paralyzing depressions, and tries to escape the legacy of his bipolar father, who had committed suicide. The original intent of the film had been to tell a story about successfully living with--and managing--a mental illness. When that Hollywood ending proves to be desperately elusive, the filmmaker and the subject are forced to ask themselves "When do you turn off the camera?"
Originally released as a motion picture in 2007
Cinematographer, Ben Selkow ; editor, John Mims ; music, Hajo Carl.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Manic-depressive illness; Manic-depressive persons; Documentary films; Internet videos; Feature films; Streaming video